Slip rate of trench‐parallel normal faulting along the Mejillones Fault (Atacama Fault System): Relationships with the northern Chile subduction and implications for seismic hazards. (20th May 2019) - Ritz, Jean‐François; Braucher, Régis; Bourlès, Didier; Delouis, Bertrand; Marquardt, Carlos; Lavenu, Alain; Philip, Hervé; Ortlieb, Luc
Abstract: The recent tectonics of the arid northern Chile Andean western forearc is characterized by trench‐parallel normal faults within the Atacama Fault System (AFS). Since the 1995‐Mw 8.1 Antofagasta earthquake, the mechanism driving this recent and localized extension is considered to be associated with the seismic cycle within the subduction zone. Analyzing morphotectonic patterns along these faults allows examining the seismic potential associated with the subduction zone. Using field Digital Elevation Models and in situ‐produced cosmogenic 10 Be, we determined a 0.2 mm/a long‐term slip rate along the Mejillones Fault, one of the most prominent structures within the AFS. This result suggests that the AFS corresponds to slow slip rate faults despite the rapid subduction context. However, the size of coseismic slips observed along the AFS faults suggests that larger subduction earthquakes (Mw > 8.1) may occur episodically in the area.